A skin cancer prevention photoageing intervention for secondary schools in Brazil delivered by medical students: protocol for a randomised controlled trial. Issue 3 (6th March 2018) - Brinker, Titus Josef; Faria, Bianca Lisa; Gatzka, Martina; de Faria, Olber Moreira; Heppt, Markus V; Kirchberger, Michael C; Schadendorf, Dirk; Nakamura, Yasuhiro; Buslaff, Fabian; Lisboa, Oscar Campos; Oliveira, Ana Carla Cruz; Lino, Henrique Augusto; et al.
Abstract : Introduction: The incidence of melanoma is increasing faster than any other major cancer both in Brazil and worldwide. The Southeast of Brazil has especially high incidences of melanoma, and early detection is low. Exposure to UV radiation represents a primary risk factor for developing melanoma. Increasing attractiveness is a major motivation for adolescents for tanning. A medical student-delivered intervention that harnesses the broad availability of mobile phones as well as adolescents' interest in their appearance may represent a novel method to improve skin cancer prevention. Methods and analysis: We developed a free mobile app (Sunface), which will be implemented in at least 30 secondary school classes, each with 21 students (at least 30 classes with 21 students for control) in February 2018 in Southeast Brazil via a novel method called mirroring. In a 45 min classroom seminar, the students' altered three-dimensional selfies on tablets are 'mirrored' via a projector in front of their entire class, showing the effects of unprotected UV exposure on their future faces. External block randomisation via computer is performed on the class level with a 1:1 allocation. Sociodemographic data, as well as skin type, ancestry, UV protection behaviour and its predictors are measured via a paper–pencil questionnaire before as well as at 3 and 6 months postintervention. The primary end point is the group difference in the 30-day prevalence of daily sunscreen use at a 6-month follow-up. Secondary end points include (1) the difference in daily sunscreen use at a 3-month follow-up, (2) if a self-skin examination in accordance with the ABCDE rule was performed within the 6-month follow-up and (3) the number of tanning sessions. Ethics and dissemination: Ethical approval was obtained from the ethics committee of the University of Itauna. Results will be disseminated at conferences and in peer-reviewed journals. Trial registration number: NCT03178240 ; Pre-results.